2001
DOI: 10.1089/109662001753165738
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of a Dietary Antioxidant Silicate Supplement, Microhydrin®, on Cardiovascular Responses to Exercise

Abstract: Amorphous silicate minerals, often described as rock flour, were once common in natural water sources and abundant in glacial stream waters. Not only do the silica mineral particles bond water and other elements for transport; they also can be adsorbed with reduced hydrogen, which releases electrons, providing antioxidant or reducing potential to surrounding fluids. The purpose of this investigation was to examine the cardiovascular responses during exercise after consumption of a dietary silicate mineral anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
24
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 15 publications
2
24
1
Order By: Relevance
“…Blood lactate concentrations were assessed 5 min before the start of exercise and 5 min after the time trial. The authors found MAC supplementation to have no effect on timetrial performance, but blood lactate was significantly reduced 5 min postexercise when participants consumed the MAC compared with placebo (Purdy Lloyd et al, 2001). A later investigation with a similar protocol found MAC supplementation to have no effect on time-trial performance, blood lactate, or energy substrate utilization in highly trained male cyclists (65.3 ± 1.2 ml • kg -1 • min -1 ; Glazier et al, 2004).…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Blood lactate concentrations were assessed 5 min before the start of exercise and 5 min after the time trial. The authors found MAC supplementation to have no effect on timetrial performance, but blood lactate was significantly reduced 5 min postexercise when participants consumed the MAC compared with placebo (Purdy Lloyd et al, 2001). A later investigation with a similar protocol found MAC supplementation to have no effect on time-trial performance, blood lactate, or energy substrate utilization in highly trained male cyclists (65.3 ± 1.2 ml • kg -1 • min -1 ; Glazier et al, 2004).…”
mentioning
confidence: 97%
“…As mentioned previously, evidence of the silica-water interface can be seen through an increased ability to buffer changes in hydrogen-ion status and metabolic accumulation of lactate. In this respect, previous investigations have suggested that MAC supplementation may affect changes in lactate accumulation and therefore affect prolonged exercise (Purdy Lloyd et al, 2001).…”
mentioning
confidence: 98%
See 3 more Smart Citations